Designing skills for life skills education plan of pedagogical students in Vietnam - Giang, Trinh Thuy; Khanh, Mai Quoc; Hong, Nguyen Thi Thanh; Hoa, Vu Le (International research journal of management, IT and social sciences, 2022)
How to organize educational activities in general and life skills education in particular at all levels to achieve the desired effect is a matter of concern to the Ministry of Education and Training of Vietnam along with schools, especially after the Ministry of Education promulgates the 2018 general education program, life skills education had become an even more important role in the good implementation of educational goals for students at all levels. The 2018 general education program is gradually being implemented according to the approved roadmap in the coming years in Vietnam, which has been placing high demands on the educational capacity of high school teachers. However, at present, whether high school teachers are able to meet the requirements of educational capacity in general and the capacity to teach life skills for students in particular is a question that is being asked by all levels of management.